E-111 Efficacy and safety of robotic stereotactic assistance (rosa) device for minimally invasive placement of intraparenchymal hematoma and intraventricular catheters: case series. (22nd July 2019) - Alan, N; Kokkinos, V; Faraji, A; Agarwal, N; Jankowitz, B
Abstract : Background: In patients with supratentorial spontaneous intracerebral hemorrhage (ICH), intrahematomal catheter placement may allow for clot thrombolysis and drainage. Robotic assistance may be used for the stereotactic placement of catheters. Objective: To describe efficacy and safety of stereotactic robotic assistance for placement of intrahematomal catheters. Methods: From 2017–2018, 4 patients with average age 64 year old (three females, one male) who presented with supratentorial ICH underwent placement of intrahematomal catheter using stereotactic robotic assistance. Postoperatively, alteplase was delivered via the catheters to the clot and the hematoma drained. Results: A total of 9 catheters were placed. The time from last seen well to incision in the operating room was between 38 to 48 hours. Average volume of ICH at initial presentation was 52 cc (29–68 cc) on volumetric analysis. Average dose of alteplase postoperatively was 6 mg (range 5–9 mg), delivered over 32.5 hours (range 18–46 hours). Average volume of ICH at 12 hours after last dose of alteplase was 13 cc (range 2–34 cc) resulting in an average reduction of 39 cc (77 ± 24%). Output from the drains were 102–872 cc (average of 561 cc). Average error associated with catheter placement at its tip was 3.3 mm ± 2.0 mm, when comparing preoperative planned trajectory to immediate postoperative scan. Conclusion: Stereotactic robotic assistance was used safely and effectively for thrombolysis and drainage of supratentorial intracerebral hemorrhage. Disclosures: N. Alan: None. V. Kokkinos: None. A. Faraji: None. N. Agarwal: None. B. Jankowitz: None.